Racionalidade dialética entre mito e esclarecimento :uma leitura da Dialética do esclarecimento, de T. W. Adorno e M. Horkheimer - Mass, Olmaro Paulo (2011)
This study investigates the criticism made by Theodor Adorno and Max Horkheimer to the modern concept of rationality in the Dialectics of Enlightenment, which is essentially focalized in the promises of the Aufklärung. When they broached the origin of Western logos in a succinct and unique form , realized that the genealogy of knowledge, they perceived that the core is in the dramatic and incontrollable need of the human being to have a self-reliance before the forces of nature which imposes fear. Therefore, the concept of enlightenment can not be understood only in light of eighteenth. For the authors, in the myth there was a knowledge, which is intuitive, explanatory and inseparable from the clarifier thought. This aimed to give explanations and justifications about the events of the relationship between human being and nature. Therefore, i every resistance in the attempt to dominate nature, human beings will increase his potential, his strength and power over it. Thus, the starting point of the Dialectics of Enlightenment is a critique of the enlighten society and modern rationality, which has become instrumental. They make us realize the limits of modernity, reason and science, the more subtle and aggressive aspects that were already present in the mutual relationship between myth and enlightenment. Though the topic broached 'rational dialectic between myth and enlightenment' constitutes the course of this dissertation, it is important to review the question which the authors used to do: why mankind is sinking into a new kind of barbarism? Faced with this question they investigate critically and deepen the strategic and instrumental knowledge that became a mechanism of power and repression. With the thesis that the myth is elucidation and elucidation has become mythology, also shows that modern rationality, under the 'lights' of the reason, has its regression germ in everywhere. The research is developed in three stages: the first chapter includes the context and the sources of the main philosophical questions of the opus Dialectic of Elucidation; the second presents Odysseus as the prototype of modern man from the tour I; Finally, the last chapter deals with the dialectic rationality between myth and elucidation